A qualitive approach to profiling gastronomes from their food experience journey - Hendijani, Roozbeh Babolian (2014)
The number of people who travel with the primary reason of gastronomic experience, termed gastronomes, is in the rise. This niche group of consumers offers an opportunity to the development of food tourism. Regrettably, only limited studies had been conducted. The urge to undertake the current research is further substantiated by the absent of insights to the underlying drives of gastronomes travel with the purpose of food hunting. To bridge the gap, this research was executed via two studies to address four objectives. First, it aims to map gastronomes’ thoughts and feelings through their mental maps. Second, it seeks to reveal the core value of food hunting attached by gastronomes through the elicitation of the deep metaphors. Third, it attempts to describe the development of behavior and interest among gastronomes. Finally, it intends to depict the typology of gastronomes. Considering the advantages of interpretivism paradigm, this research adopted Zaltman Metaphor Elicitation Technique (ZMET), an emerging powerful qualitative method to understand the gastronomes’ food hunting behavior, a project-based leisure activity, through their own voice. Both studies sampled respondents who were highly involved in this activity. The participants were recruited through purposive and snowball sampling and they came from different states in Malaysia. Study 1 focused on gastronomes thoughts and feelings underlying their behaviors of food hunting. Twelve participants were recruited. Aggregating the individual mental maps, the consensus map revealed four broad themes about food hunting shared among the participants which are (i) connection/sharing, (ii) transformation, (iii) searching as discovery, and (iv) searching as adventure. These broad themes symbolize four aspects which gastronomes associated in food hunting. Therefore, different gastronomes may find food hunting equally involving, but for different reasons. In addition, the study also yielded four prominent deep metaphors, namely journey, transformation, container, and balance. Taking the results from consensus map and metaphors, the postulation that food hunting is a behavior developed or progress over time was corroborated. Consequently, the second study was carried out. Study 2 aimed to identify the various developmental stages and the respective characteristics. Fourteen participants were recruited. The results of this study revealed that food hunting activity or behavior followed a three stage development process. The typology of the gastronomes at different stage was presented. The first stage was labeled as seed. At this stage, the food itself triggered the participants’ attention. Family members (e.g. parents and grandparents) were the major influencers at this stage. The second stage was named sapling. At this stage, interest in food hunting began to develop among participants. Their searching of food was greatly influenced by media such as food-related TV program, internet, and blogs. The final stage termed as tree. At this stage, participants were knowledgeable about this activity. They became the reference or opinion leader to others. This research contributes towards the theoretical explanations of gastronomes’ behavior by deeper understanding of their thoughts and feelings. In particular, the consensus map is important to conceptualize the relationships between thoughts and feelings that determine the gastronomes’ food hunting behavior. The four broad themes of food hunting identified in this research are powerful bases for market segmentation because they frame how gastronomes see and participate in food hunting. This model offers destination marketers and industrial practitioners a framework to access meanings necessary to understand gastronomes’ behavior. This model also will help tourism marketers to have a detailed examination of gastronomy tourism market and it demands. In terms of practical implication, knowing the characteristics of gastronomes will help destination marketers to have a better marketing strategy communication. An appreciation of how and why gastronomes participate in food hunting is valuable for tourism marketers in predicting precise market demands and it values. The typology with characteristics of gastronomes in different stages offers researchers and marketers an appealing way to think about change in leisure participation. Most of the marketing messages are relating to providing new experience and environment to trigger the attention of food tourists. This study examined the value of food hunting from the perspective of consumer behavior and argued that underlying motives, such as human emotion, can significantly challenge the current value assessment models which commonly used in today’s market. Results revealed that the value of participating in this activity is not merely to gain novel sensory experiences, but also to actively seek for positive feelings and ideals that gastronomes associate with food hunting. One of the pursuits was to broaden their world view.